Cell Tracking by Magnetic Particle Imaging: Methodology for Labeling THP-1 Monocytes with Magnetic Nanoparticles for Cellular Imaging - Amani Remmo; Norbert Löwa; Olaf Kosch; Dietmar Eberbeck; Antje Ludwig; Lena Kampen; Cordula Grüttner; Frank Wiekhorst (Cells, 2022)
Magnetic particle imaging (MPI) is a noninvasive tomographic imaging modality for the quantitative visualization of magnetic nanoparticles (MNPs) with high temporal and spatial resolution. The general capability of MPI for cell tracking (e.g., monitoring living cells labeled with MNPs) has successfully been shown. MNPs in cell culture media are often subjected to structural and magnetic changes. In addition to the deteriorating reproducibility, this also complicates the systematic study of the relationship between the MNP properties and their cellular uptake for MPI. Here, we present a method for the preparation of magnetically labeled THP-1 (Tamm–Horsfall Protein-1) monocytes that are used in MPI cell tracking. The method development was performed using two different MPI tracers, which exhibited electrostatic and steric stabilizations, respectively. In the first step, the interaction between the MNPs and cell culture media was investigated and adjusted to ensure high structural and magnetic stability. Furthermore, the influences of the incubation time, MNP concentration used for cellular uptake, and individual preparation steps (e.g., the washing of cells) were systematically investigated. Finally, the success of the developed loading method was demonstrated by the MPI measurements. The presented systematic investigation of the factors that influence the MNP loading of cells will help to develop a reliable and reproducible method for MPI monocyte tracking for the early detection of inflammation in the future.